Long-Term Outcomes of Childhood Left Ventricular Noncompaction Cardiomyopathy: Results From a National Population-Based Study. Issue 4 (24th July 2018) - Shi, William Y.; Moreno-Betancur, Margarita; Nugent, Alan W.; Cheung, Michael; Colan, Steven; Turner, Christian; Sholler, Gary F.; Robertson, Terry; Justo, Robert; Bullock, Andrew; King, Ingrid; Davis, Andrew M.; et al.
Abstract : Background: Long-term outcomes for childhood left ventricular noncompaction (LVNC) are uncertain. We examined late outcomes for children with LVNC enrolled in a national population-based study. Methods: The National Australian Childhood Cardiomyopathy Study includes all children in Australia with primary cardiomyopathy diagnosed before 10 years of age between 1987 and 1996. Outcomes for subjects with LVNC with a dilated phenotype (LVNC-D) were compared with outcomes for those with dilated cardiomyopathy. Propensity-score analysis was used for risk factor adjustment. Results: There were 29 subjects with LVNC (9.2% of all cardiomyopathy subjects), with a mean annual incidence of newly diagnosed cases of 0.11 per 100 000 at-risk individuals. Congestive heart failure was the initial symptom in 24 of 29 subjects (83%), and 27 (93%) had LVNC-D. The median age at diagnosis was 0.3 (interquartile interval, 0.08–1.3) years. The median duration of follow-up was 6.8 (interquartile interval, 0.7–24.0) years for all subjects and 24.7 (interquartile interval, 23.3 – 27.7) years for surviving subjects. Freedom from death or transplantation was 48% (95% confidence interval [CI], 30–65) at 10 years after diagnosis and 45% (95% CI, 27–63) at 15 years. In competing-risk analysis, 21% of subjects with LVNC were alive with normal left ventricular systolic function, and 31% were alive with abnormal function at 15 years. Propensity-score matching between subjects with LVNC-D and those with dilated cardiomyopathy suggested a lower freedom from death/transplantation at 15 years after diagnosis in the subjects with LVNC-D (LVNC-D, 46% [95% CI, 26–66] versus dilated cardiomyopathy, 70% [95% CI, 42–97]; P =0.08). Using propensity-score inverse probability of treatment–weighted Cox regression, we found evidence that LVNC-D was associated with a greater risk of death or transplantation (hazard ratio, 2.3; 95% CI, 1.4–3.8; P =0.0012). Conclusions: Symptomatic children with LVNC usually present in early infancy with a predominant dilated phenotype. Long-term outcomes are worse than for matched children with dilated cardiomyopathy.